Cellulose enzymatic saccharification and preparation of 5-hydroxymethylfurfural based on bamboo hydrolysis residue separation in ionic liquids. Issue 49 (14th June 2017) - Kassanov, Bekbolat; Wang, Ju; Fu, Yan; Chang, Jie
Abstract : Ionic liquid/ethanol was used in bamboo hydrolysis residue (BHR) to separate lignin and cellulose. Abstract : Ionic liquid/ethanol was used in bamboo hydrolysis residue (BHR) to separate lignin and cellulose. The optimal dissolution conditions were as follows: 160 °C, 150 min, 1 : 1 of volume ratio of [AMIM]Cl to ethanol, 1 : 10 of mass ratio of solid to liquid, when the dissolution rate was 41.7%, the purity of crude lignin was 86.7%, while that of cellulose product was 92.0%. Additionally the recycling effect of [AMIM]Cl/ethanol was ideal. The crystal structure of cellulose had not been destroyed; its crystallinity increased. Cellulose enzymatic saccharification was investigated, and the optimum process conditions were as follows: 50 °C, 48 h, 2 g L −1 of cellulase concentration, pH = 4.5, when the saccharification yield reached 83.7%. The cellulose crystal structure was destroyed and its degree of crystallinity was decreased after saccharification. Then the monosaccharide was used to convert to 5-hydroxymethylfurfural (5-HMF) under Brønsted acids or Lewis acids catalysis in [AMIM]OAc. It was found that the catalytic effect of Lewis acids was much better than that of Brønsted acids investigated, especially CrCl3 . Choosing CrCl3 as catalyst, the optimum process conditions were as follows: 1 : 10 of mass ratio of solid to liquid, 10 mol% (based on monosaccharide) CrCl3, 160 °C, 3 h, when the 5-HMF yield reached 56.8%.